Medico-botanical studies of Sandwip island in Chittagong, Bangladesh - Sajib, Noor Hassan; Uddin, S. B. (Bangladesh Journal of Plant Taxonomy, 2013)
A study of the plant diversity of Sandwip Island has been conducted during July 2008 to April 2011 in order to document plant species used as traditional herbal medicine. A total of 111 species under 93 genera of 53 families have been documented which are used for the treatment of 48 diseases/illness. The local people of the island mostly depended on herbal medicine for their primary health care. Twenty one recorded medicinal plant species are used for the treatment of various types of pain, 14 each for dysentery and rheumatism, 8 each for cough and haemorrhages, 7 for skin diseases, 6 for worms, 5 for boils, 4 each for jaundice and fracture, 3 each for chicken pox, fever and diabetes and 54 for other diseases. DOI: http://dx.doi.org/10.3329/bjpt.v20i1.15463 Bangladesh J. Plant Taxon. 20(1): 39-49, 2013 (June)